KAJIAN TERHADAP VARIASI BENTUK MOTIF, TEKNIK PEMBUATAN, DAN JENIS PRODUK BORDIR MASIN ITAM DI KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Rahmad Kurniawan Putra, Dra. Minarsih, M.Sn., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2017)
Embroidery Indonesia each area has its own characteristics. One of them in West Sumatra. Coastal varied embroidery such as Pesisir embroidery, Pariaman, and Bukittinggi. Embroidery in District Ampek Angkek, Agam, West Sumatra, also has a distinctive type of embroidery called masin itam embroidery. The focus of the study (1) Variations motif; (2) The technique of making; (3) The types of masin itam embroidery products. Through qualitative research results obtained: naturalist motifs form and decorative; the technique of making are suji cair and Kerancang; The resulting products are disposable items: mukena, baju kebaya, baju kuruang, koko, veil or scarf, bed linen, bed-sets of the bride, and pedestal table.Kata Kunci : Variasi Bentuk Motif, Teknik Pembuatan, dan Jenis Produk